2021 European Control Conference (ECC) 2021
DOI: 10.23919/ecc54610.2021.9654844
|View full text |Cite
|
Sign up to set email alerts
|

Observability of Singular Linear Switched Systems in Discrete Time: Single Switch Case

Abstract: In this paper, we investigate the observability of singular linear switched systems in discrete time. As a preliminary study, we restrict ourselves to systems with a single switch switching signal, i.e. the system switches from one mode to another mode at a certain switching time. We provide two necessary and sufficient conditions for the observability characterization. The first condition is applied for arbitrary switching time and the second one is for switching times that are far enough from the initial tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…Utilizing Lemma 3.6 proves that it is not possible to have different observability properties with different switching times, which is omitted due to space limitation. This result is indeed stronger than the result presented in [16,Corr. 3.4] where we have now confirmed that the observability of LSSs, with any dimensional states and under a single switch switching signal, is always constant as long as each mode is long enough active.…”
Section: B Observability and Determinability Definitionscontrasting
confidence: 61%
See 3 more Smart Citations
“…Utilizing Lemma 3.6 proves that it is not possible to have different observability properties with different switching times, which is omitted due to space limitation. This result is indeed stronger than the result presented in [16,Corr. 3.4] where we have now confirmed that the observability of LSSs, with any dimensional states and under a single switch switching signal, is always constant as long as each mode is long enough active.…”
Section: B Observability and Determinability Definitionscontrasting
confidence: 61%
“…III. OBSERVABILITY Under a single switch switching signal, the observability characterization for (2) has been covered in [16]. We present in the following the results regarding the observability characterizations for general switching signals.…”
Section: B Observability and Determinability Definitionsmentioning
confidence: 99%
See 2 more Smart Citations